Papel da metilação de histonas H3 nos efeitos toxicológicos do metilmercúrio e/ou palmitato de retinol em ratos Wistar - Kessler, Flávio Gabriel Carazza (2020)
Methylmercury (MeHg) is a pollutant present in fish, being seafood consumption the main route of contamination. It was already demonstrated the MeHg’s capability to cause neurodevelopment impairments and cognitive deficits in offspring and children after gestation exposure. Vitamin A, a fish micronutrient, is an essential molecule, but high doses can lead to cognitive dysfunctions and even teratogenesis. Moreover, vitamin A is also recommended for supplementation on pregnants. Doses considered low for both MeHg and vitamin A can establish toxicological effects and influence histone modifications, DNA methylation and non-coding RNAs expression. Besides, these effects seem to be perpetuated by transgenerational inheritance. This work consisted of administrating low doses of MeHg (0.5mg/kg/day) and/or retinyl palmitate (VitA, 7500 retinol activity equivalents/kg/day) to Wistar rats (F0) during gestation and lactation. It evaluates the effects in subsequent generations (F1 and F2). The exposures were capable to influence neurobehavior, organs weight, cytogenetic damage and histone methylation until F2. MeHg and VitA interaction in co-exposure group is conflicting, in eye-opening time, a neurobehaviour test, the effect appeared to be synergistic. However, the organs weight of the co-exposure group was at control level in nearly all parameters. This work is the very first to determine the transgenerational inheritance of toxicological effects of environmental co-exposure to MeHg and/or VitA. Thus, these compounds are capable to induce health injury and epigenetic modulations of histone H3. Our data suggests that populations in high exposed areas to MeHg and/or VitA may be affected for more than one generation once exposure has finished.